Innovations in intracranial aneurysm treatment: a pilot study on the Choydar flow diverter - Liu, Changya; Cai, Yike; Zang, Chunguang; Guo, Kaikai; Hu, Xuebin (Frontiers in Neurology, 2024)
Abstract: Background: The flow diverter (FD) has emerged as a promising treatment option for intracranial aneurysms. Recently, a novel flow-diverting stent, the Choydar FD device, has been developed within our nation. Objective: To introduce the newly developed Choydar FD device and present our preliminary clinical experience with its application in the treatment of intracranial aneurysms. Methods: A total of 23 patients with 23 unruptured intracranial aneurysms, comprising 20 (87.0%) aneurysms located at the internal carotid artery and 3 (13.0%) at the vertebral artery, were treated with the Choydar FD device between December 2021 and April 2022. Patient baseline data, clinical and angiographic outcomes were collected and analyzed. Results: The Choydar FD device was successfully deployed in all patients (100%), with 18 aneurysms (78.3%) additionally treated with coils. One patient experienced an ischemic event with sensory disturbance during the perioperative period. At the 1-year follow-up, all patients demonstrated good clinical outcomes. Of the 23 aneurysms with available angiographic follow-up, 22 (95.7%) achieved complete occlusion, and one patient exhibited in-stent stenosis without neurological deficits. Conclusion: The initial clinical results of the Choydar FD device are encouraging, and it appears to be a useful option for treating intracranial aneurysms with acceptable efficacy and safety. Future studies with larger sample sizes and longer follow-up durations are warranted to validate these findings.